Inhibition of human prostate smooth muscle contraction by the inhibitors of protein kinase C, GF109203X, and Go6983. Issue 1 (11th October 2021) - Huang, Ru; Liu, Yuhan; Li, Bingsheng; Wang, Ruixiao; Tamalunas, Alexander; Waidelich, Raphaela; Strittmatter, Frank; Stief, Christian G.; Hennenberg, Martin
Abstract: Introduction: Prostate smooth muscle contraction is promoted by receptor‐induced activation of intracellular signaling pathways. The presumed involvement in etiology and medical treatment of lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH) imparts a high clinical relevance to prostate smooth muscle contraction, which is contrasted by incomplete understanding at the molecular level. Involvement of protein kinase C (PKC) has been commonly assumed, but available studies were limited to nonhuman prostate smooth muscle or cell cultures. Here, we examined the effects of the PKC inhibitors Go6983 and GF109203x on contractions of human prostate tissues. Methods: Prostate tissues were obtained from radical prostatectomy. Contractions were induced by electric field stimulation (EFS), α 1 ‐adrenergic agonists (noradrenaline, phenylephrine, methoxamine), thromboxane A2 analog U46619, endothelin‐1, or calcium chloride in an organ bath. Results: GF109203X (500 nM) and Go6983 (300 nM) reduced EFS‐, noradrenaline‐, phenylephrine‐, methoxamine‐, and U46619‐induced contractions of human prostate tissues, with maximum inhibitions approaching up to 55%. Using concentrations of 3 µM, GF109203X and Go6983 inhibited EFS‐ and noradrenaline‐induced contractions, with similar effect sizes as 500 and 300 nM, respectively. Endothelin‐1‐induced contractions were not inhibited by GF109203X, and to neglectable extent by Go6983. After depolarization in calcium‐free solution, calcium chloride‐induced concentration‐dependent contractions, which were inhibited by GF109203X and Go6983. Conclusions: GF109203X and Go6983 inhibit neurogenic, α 1 ‐adrenergic, and thromboxane A2 ‐induced smooth muscle contractions in the human prostate, suggesting a role of PKC for human prostate smooth muscle contraction. The inhibition may by be imparted by inhibition of calcium sensitivity.